Eruption dynamics within an emergent subglacial setting: a case study of the 2004 eruption of Grímsvötn volcano, Iceland - Jude-Eton, Tanya Chantal; Eton, Tanya Chantal Jude (The University of Edinburgh, 2013)
The November 2004 explosive eruption of Grímsvötn volcano, Iceland (G2004) commenced as a subglacial event within the interior of the Vatnajökull ice cap before breaking through the ice cover to generate a 6-10 km high eruption column. This produced a tephra apron extending >50 km across the ice surface northwards from the eruption site, incorporating 0.047 km3 (DRE) of plagioclase-bearing, sparsely porphyritic, basaltic tephra. This study focuses on quantifying the key eruption parameters and evaluating the stratigraphy, grain size and geochemical characteristics of the proximal facies of the subaerial deposit with a level of detail and precision that has never previously been possible for a modern glacio-volcanic event. The G2004 deposit consists of a finely layered sequence which is subdivided into seven units (A-G) on the basis of differences in texture, grain size and componentry and the presence of sharp contacts between the layers. It is poorly sorted and finegrained with a median clast diameter of 1.5 Φ. The grain size characteristics and clast morphologies are indicative of intense phreatomagmatic fragmentation, despite a significant component of highly vesicular juvenile glass. A wide range in thicknesses and geometries of depositional units reflects variations in intensity and style of activity. Units C and E account for 80% of the total deposit volume, including the entire distal portion, and are interpreted to represent a mixture of (i) a widely dispersed component that fell from the upper margins of a strongly inclined (~45°) 6-10 km high plume and (ii) a locally dispersed (<3 km from source) component originating from (1) pyroclastic density currents generated by shallow explosions and tephra jets and (2) sedimentation from the jet region and lower convective column margins. The other units are only locally dispersed around the vent. A significant proportion of fine material was deposited in the near-vent region due to particle aggregation processes. The bulk of the G2004 deposit is ...